Multi-responsive micro/nanogels for optical sensing. Issue 1 (31st December 2022) - Shu, Tong; Hu, Liang; Hunter, Haley; Balasuriya, Nicholas; Fang, Changhao; Zhang, Qiang; Serpe, Michael J.
ABSTRACT: Micro/nanogels are unique materials that exhibit the properties of both colloids and hydrogels, i.e. being colloids they exhibit a large specific surface area, while they are hydrophilic and porous allowing them to swell to a great degree with water. Engineering micro/nanogels, through the rational design of various polymer compositions and/or optical structures, can enable them to respond to a myriad of stimuli, e.g. temperature, pH, biomolecules, CO2, light, and electricity. These multi-responsive micro/nanogels and their assemblies, are capable of recognizing and transducing analyte signals into changes in optical properties observable spectroscopically or via the naked eye, allowing their use as optical sensors. In this review, we have highlighted recent state-of-the-art examples of stimuli-responsive micro/nanogel-based systems for optical sensors. Graphical Abstract: uf0001